1993
DOI: 10.1063/1.464116
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation dynamics of CH3SH at 222, 248, and 193 nm: An analog for probing nonadiabaticity in the transition state region of bimolecular reactions

Abstract: CH3SH ultraviolet absorption cross sections in the region 192.5-309.5 nm and photodecomposition at 222 and 193 nm and 296 K A crossed lasermolecular beam study of the one and two photon dissociation dynamics of ferrocene at 193 and 248 nm These experiments use molecular photodissociation of CH 3 SH to probe the dynamics and the influence of nonadiabatic coupling in the transition state region of the CH 3 +SH--+CH 3 S+H reaction. Photoexcitation at 222 and 248 nm in the first of two absorption bands accesses th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Alternatively, when the molecule is excited at 193 nm in the higher energy absorption band, it is promoted to the upper bound adiabat-the 2 1 A surface-where it dissociates via nonadiabatic coupling to the transition state region of the lower adiabat. Photofragment velocity and angular distribution measurements on CH 3 -S-H at 193 nm show that the nonadiabatic decay to the transition-state region of the lower surface occurs in less than a picosecond and results in a factor of eight larger branching for decay of the transition state complex to the CH 3 + SH exit channel than direct excitation to the lower adiabat at 222 nm (90)(91)(92). The larger branching ratio results from the stretching of the C-S bond on the upper adiabat, evidenced in emission spectroscopy experiments (93).…”
Section: Probing Nonadiabatic Effects At the Transition Statementioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, when the molecule is excited at 193 nm in the higher energy absorption band, it is promoted to the upper bound adiabat-the 2 1 A surface-where it dissociates via nonadiabatic coupling to the transition state region of the lower adiabat. Photofragment velocity and angular distribution measurements on CH 3 -S-H at 193 nm show that the nonadiabatic decay to the transition-state region of the lower surface occurs in less than a picosecond and results in a factor of eight larger branching for decay of the transition state complex to the CH 3 + SH exit channel than direct excitation to the lower adiabat at 222 nm (90)(91)(92). The larger branching ratio results from the stretching of the C-S bond on the upper adiabat, evidenced in emission spectroscopy experiments (93).…”
Section: Probing Nonadiabatic Effects At the Transition Statementioning
confidence: 99%
“…One can do just that with the excited state reaction CH 3 S + H → CH 3 + SH (90). As depicted schematically in Figure 13, excitation of CH 3 SH at 222 nm offers Franck-Condon access to a region near the transition state on the lower adiabatic potential energy surface-the 1 1 A surface-for the excited state bimolecular reaction, since the geometry of CH 3 SH in the ground electronic state is close to that of the transition state on the 1 1 A surface.…”
Section: Probing Nonadiabatic Effects At the Transition Statementioning
confidence: 99%
“…Kawaguchi et al identified HCCNC 44 and later the same year HNCCC 45 in Taurus Molecular Cloud 1 (TMC-1). Gensheimer et al 46 Photolysis of thiol species of the form R-SH results mainly in scission of C-S and S-H bonds 52,53,54 with the main products being radicals and, depending on photolysis conditions, various radical recombination products. In 195 nm flash photolysis experiments on gaseous CH 3 SH Callear et al 52 Hydrogen atom production and escape of H 2 from the matrix cage has been reported as well, producing even more complex, dehydrogenated species, where photolysis of methanethiol at 121nm in a nitrogen matrix at 14 K leads to formation of CH 4 , CS, CS 2 , CH 3 and H 2 CS as the main products 58 .…”
Section: Concerning Isomerization Of Cyano Species Uv Irradiation Ofmentioning
confidence: 99%
“…The UV photodissociation dynamics of CH 3 SH has been extensively investigated previously [2][3][4][5][6][7][8][9]. Experimental and theoretical results indicate that photodissociation of CH 3 SH in the UV region occurs primarily through the direct fission of the S-H bond via a perpendicular electronic excitation.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental and theoretical results indicate that photodissociation of CH 3 SH in the UV region occurs primarily through the direct fission of the S-H bond via a perpendicular electronic excitation. Even though the UV photodissociation dynamics of CH 3 SH has been well understood, photodissociation of CH 3 CH 2 SH and C 3 H 7 SH (both CH 3 CH 2 CH 3 SH and CH 3 CHðSHÞ CH 3 ) have received little attention. In this work, the velocity map ion-imaging technique was employed to study the H-atom elimination from the above three compounds at the photolysis wavelength of 243 nm, at which the radiation in the low atmospheric region from the Sun is still significant.…”
Section: Introductionmentioning
confidence: 99%